Pelaksanaan Fungsi Controlling Dewan Perwakilan Rakyat Daerah dalam Pembangunan Drainase Kota Bukittinggi - Zikry, Muhammad; Haskar, Edi; Farda, Nessa Fajriyana (UNES Law Review, 2023)
The purpose of this study is to determine the implementation of the supervisory function of the Regional People's Representative Council of the City of Bukittinggi in the 2021-2022 drainage development project. The drainage project implemented by the Bukittinggi city government has had an impact on community activities. Therefore, the role of people's representative institutions is needed to oversee so that good governance is realized. This research is descriptive in nature, namely research that aims to obtain a complete picture (description) of the legal situation that applies in a certain place, using an empirical juridical approach. The data sources consist of primary data and secondary data. Based on the results of the research, the supervisory function of the Regional Representatives Council of the City of Bukittinggi has not been carried out optimally. The form of implementation of the supervisory function is by summoning the relevant offices for hearings and conducting field inspections. The obstacle faced in carrying out the supervisory function by the Regional People's Legislative Assembly for the City of Bukittinggi is the lack of responsibility for members of the council in carrying out their duties according to their authority, as regulated by law.